Thalassaemia in children: from quality of care to quality of life. Issue 11 (19th August 2015) - Amid, Ali; Saliba, Antoine N; Taher, Ali T; Klaassen, Robert J
Abstract : Over the past few decades, there has been a remarkable improvement in the survival of patients with thalassaemia in developed countries. Availability of safe blood transfusions, effective and accessible iron chelating medications, the introduction of new and non-invasive methods of tissue iron assessment and other advances in multidisciplinary care of thalassaemia patients have all contributed to better outcomes. This, however, may not be true for patients who are born in countries where the resources are limited. Unfortunately, transfusion-transmitted infections are still major concerns in these countries where paradoxically thalassaemia is most common. Moreover, oral iron chelators and MRI for monitoring of iron status may not be widely accessible or affordable, which may result in poor compliance and suboptimal iron chelation. All of these limitations will lead to reduced survival and increased thalassaemia-related complications and subsequently will affect the patient's quality of life. In countries with limited resources, together with improvement of clinical care, strategies to control the disease burden, such as public education, screening programmes and appropriate counselling, should be put in place. Much can be done to improve the situation by developing partnerships between developed countries and those with limited resources. Future research should also particularly focus on patient's quality of life as an important outcome of care.